A Retrospective Comparative Study of Two Concentrations of Intralesional Triamcinolone Acetonide in the Treatment of Patchy Alopecia Areata on the Scalp - Muhaidat JM (Clinical, Cosmetic and Investigational Dermatology, 2020)
Jihan M Muhaidat,1 Firas Al-Qarqaz,1 Yousef Khader,2 Diala M Alshiyab,1 Hadeel Alkofahi,1 Mohanad Almalekh1 1Department of Dermatology, Faculty of Medicine, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Public Health, Community Medicine, Jordan University of Science and Technology, Irbid, JordanCorrespondence: Jihan M MuhaidatDepartment of Dermatology, Faculty of Medicine, Jordan University of Science and Technology, Irbid 22110, JordanTel +96227200600Fax +96227200624Email jmmuhaidat@just.edu.joBackground: Alopecia areata (AA) usually manifests as patches of non-scarring hair loss due to immune dysregulation. Intradermal injection of steroids is considered a first-line treatment of patchy AA.Purpose: To compare the efficacy and safety of two commonly used concentrations of intralesional triamcinolone acetonide (ILT) (5 mg/mL vs 10 mg/mL) in the treatment of patchy AA on the scalp.Patients and Methods: A retrospective comparative study that included 85 patients diagnosed with patchy AA on the scalp, who were treated with monthly injections of ILT. Patients were divided into Group 1 that received 5 mg/mL and Group 2 that received 10 mg/mL. The response rate (defined as the percentage of patients who achieved complete hair regrowth) and the side effects were compared between the two groups after completion of three treatment sessions, and recurrence was assessed after 1− 3 years.Results: Demographic composition of the two groups was comparable. The difference in response rate and the side-effects between the two groups were not statistically significant. Complete hair regrowth was noted in 43.5% of patients in Group 1 and 53.8% of those in Group 2 (P=0.340). About 17% and 25% of patients in Group 1 and Group 2, respectively, developed minor local side-effects (P=0.354), and almost 45% of patients from both groups had recurrence after 1− 3 years. Disease duration exceeding 6 months correlated with poor treatment response.Conclusion: Intralesional injection of triamcinolone acetonide 5 mg/mL is equally effective and safe compared to 10 mg/mL in the treatment of patchy alopecia areata.Keywords: alopecia areata, intralesional steroids, triamcinolone acetonide